Rugged Constant-Temperature Thermal Anemometer - Labbe-Morales, R; Palma-Solorza, J (American Institute of Physics, 2016)
Here we report a robust thermal anemometer which can be easily built. It was conceived to measure outdoor wind speeds and for airspeed monitoring in wind tunnels and other indoor uses. It works at a constant, low temperature of approximately 90 °C, so that an independent measurement of the air temperature is required to give a correct speed reading. Despite the size and high thermal inertia of the probe, the test results show that this anemometer is capable of measuring turbulent fluctuations up to ∼100 Hz in winds of ∼14 m/s, which corresponds to a scale similar to the length of the probe. © 2016 Author(s).